The Inflammatory Profile of the Tumor Microenvironment, Orchestrated by Cyclooxygenase-2, Promotes Epithelial-Mesenchymal Transition - Gómez-Valenzuela, Fernán; Escobar, Enrico; Pérez-Tomás, Ricardo; Montecinos, Viviana P. (Frontiers in Oncology, 2021)
The tumor microenvironment (TME) corresponds to a complex and dynamic interconnection between the extracellular matrix and malignant cells and their surrounding stroma composed of immune and mesenchymal cells. The TME has constant cellular communication through cytokines that sustain an inflammatory profile, which favors tumor progression, angiogenesis, cell invasion, and metastasis. Although the epithelial-mesenchymal transition (EMT) represents a relevant metastasis-initiating event that promotes an invasive phenotype in malignant epithelial cells, its relationship with the inflammatory profile of the TME is poorly understood. Previous evidence strongly suggests that cyclooxygenase-2 (COX-2) overexpression, a pro-inflammatory enzyme related to chronic unresolved inflammation, is associated with common EMT-signaling pathways. This review article summarizes how COX-2 overexpression, within the context of the TME, orchestrates the EMT process and promotes initial metastatic-related events.